Screening of cadmium and lead in potentially contaminated waters using a spectrophotometric sequential injection lab-on-valve methodology - Santos, Inês C. (2016)
The present work describes the development of a µSI-LOV method for the simultaneous screening of cadmium and lead in potentially contaminated water samples. To attain the biparametric determination, dithizone was chosen as the spectrophotometric reagent as it forms a colored complex with both metal ions, at different pH conditions. The cadmium determination was attained in strong alkaline conditions (pH≈12); the lead determination was calculated by the difference with the determination of both metals in mild alkaline conditions (pH≈8). The colored complex was measured at 550 nm and the method presented a LOD of 34 μg L−1 for cadmium and 56 μg L−1 for lead, with a sample consumption of 20 µL per assay and a determination rate of 55 h−1. The results obtained were in agreement with those obtained by FAAS. The developed method was efficiently applied to the screening of cadmium and lead in marine port waters.